DEVELOPING ENGLISH ELECTRONIC MODULE USING JOB ACCESS WITH SPEECH (JAWS) AS SCREEN READER TO EMPOWER LEARNING AUTONOMY OF STUDENTS WITH SPECIAL NEED - Wiyanah, Sri (Ahmad Dahlan Journal of English Studies, 2016)
The research and development produces interesting, interactive, and suitable learning resources for students with special need, i.e., students with visually impaired in order to develop studentsâ empowerment. Development of electronic module proposes electronic resources by applying Job Access with Speech (JAWS) as screen reader on the computer to accommodate some obstacles of visually impaired students in learning English. Therefore, it is helpful for them to learn better by maximizing their potential and their restrictiveness to become creative and autonomous learners.Qualitative research was applied in this research. Data was collected from observation, interview, questionnaire and note taking in a kind of daily agenda. Data was described qualitatively. The data finding then analyzed in order to produce a suitable electronic module. The research model is Research and Development that was proposed by Borg and Gall. There are seven stages that was done, i.e. (1)Â Research and Information Collection Â (2)Â Planning (3)Â Develop Preliminary form of Product (4)Â Preliminary Field Testing (5)Â Main Product Revision (6)Â Main Field Testing (7)Â Operational Product Revision. The product of English electronic was validated by English teacher or material expert, media expert and 2 visually impaired students from different level. Instrumentsâ assessments include module organization, material, evaluation and readability, display and also programming.The findings produced a very good quality module based on teacher, students, material and media expert. Form the material, the average score was 4, 2 and the percentage was 84%. From media point of view, the average score was 3,7 and the percentage was 76. It also got good responses from the visually impaired students. They enjoyed learning with the module. They feel happy and free in learning. Moreover, the empowerment in learning could be reached. English electronic module was suitable and feasible for the visually impaired students in learning English.Â